1987
DOI: 10.3989/mc.1987.v37.i207.859
|View full text |Cite
|
Sign up to set email alerts
|

Aproximación al efecto de la resistividad del hormigón en la corrosión de armaduras embebidas en hormigón

Abstract: Aproximación al efecto de la resistividad del hormigón en la corrosión de armaduras embebidas en hormigónApproacli to tlie effect of concrete resistivity in tlie corrosion of rebars in concrete El acceso de oxígeno solamente controla la velocidad de corrosión (control catódico) cuando el hormigón está sumergido en agua, bajo el suelo o cuando ei recubrimiento del hormigón armado es > 3-4 cm (donde los poros pueden estar saturados continuamente). En hormigón aireado, el flujo de oxígeno disponible ai nivel de l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…For all the types of binder, it can be observed that the corrosion current density increased, when the environmental relative humidity increased, and hence when likely the water content in concrete increased, indicating that the presence of water in the pore system of concrete is a key parameter in determining the corrosion current density. The correlation between log(i corr ) and exposure conditions was comparable with those detected in the other works, although shifted to the bottom [13,14,17,22]. As for the electrical resistivity, temperature affected the corrosion current density when relative humidity was 90%, leading to an increase from values between 0.4 and 1 mA m −2 to values between 1.4 and 3.9 mA m −2 .…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…For all the types of binder, it can be observed that the corrosion current density increased, when the environmental relative humidity increased, and hence when likely the water content in concrete increased, indicating that the presence of water in the pore system of concrete is a key parameter in determining the corrosion current density. The correlation between log(i corr ) and exposure conditions was comparable with those detected in the other works, although shifted to the bottom [13,14,17,22]. As for the electrical resistivity, temperature affected the corrosion current density when relative humidity was 90%, leading to an increase from values between 0.4 and 1 mA m −2 to values between 1.4 and 3.9 mA m −2 .…”
Section: Resultssupporting
confidence: 84%
“…The corrosion behaviour of carbon steel bars embedded in different types of concrete was also evaluated in laboratory conditions at different values of relative humidity, within a range of 40-100%. In the 95-100% R.H. range, corrosion current density between 2 and 30 mA m −2 was detected by several authors [9][10][11][12][13][14][15][16], while decreasing the relative humidity, corrosion current density decreased approaching values between 2 and 10 mA m −2 in the 80-90% R.H. range [17,18] to values lower than 1 mA m −2 in the 60-75% R.H. range [2,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative humidity has also been found to have a considerable effect on the corrosion behavior of concrete structures both at the initiation and the propagation phases (Glass et al 1991;Lim et al 2010;Hussain 2011;Jiang and Yuan 2013). Data reported in several studies (Alonso et al 1987 suggest that corrosion rates exponentially increase with increasing water content. Other studies (Gonzalez et al 1993;López and González 1993) have shown that the maximum corrosion rate occurred at pore saturation values of 60-70%.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted among scientists that nitrates do not promote steel corrosion (Alonso and Andrade,7 D'yachenko et al 8 and Goetz9). Meland et al 10 investigated the reinforced concrete of a 22 year old calcium nitrate (containing some ammonium) production plant where the concrete was deteriorated due to external calcium nitrate/ammonium attack (probably since concentrated calcium nitrate will form the expansive double salt with calcium hydroxide).…”
Section: Introductionmentioning
confidence: 99%